PROFESIONAL GURU DALAM PENERAPAN PEMBELAJARAN DARING DI TK NEGERI PEMBINA SABAK AUH - Afriani, Depi; Okmandar, Dwi Silviani (STKIP Pesisir Selatan, 2020)
Now that there is a pandemic period, more professional teachers will be asked, in order to slow the spread of COVID-19, this pattern demands the role of the teacher. This study aims to review how teachers during the pandemic, who pay attention to aspects of bold learning (implementation, challenges, and solutions). The implementation of courage learning has challenges/obstacles, both from the aspect of human resources, infrastructure, and technical implementation. As a recommendation for the future, it requires public partnership and the involvement of many parties on an ongoing basis. In this case the researcher used data collection in the form of unstructured observations, interviews (unstructured) and documentation. The results of research conducted by researchers at the Pembina State Kindergarten of Sabak Auh have been categorized as good, although there are still a few civil servants that do not make the professionalism of the teacher decrease in the application of bold learning, seen from the teacher's performance in learning in the classroom that is shaded by each teacher: RPPH work, love letters , video creation congratulations brave(on the network)